Document Analysis of Literacy Policy and Curriculum Expectations in Primary and Lower Secondary Education in Indonesia - Desi Herayana; Hartati Suryaningsih; Sartika Hijriati; Baiq Annisa Shallaita; Sahrul Sahrul (Jurnal Ilmiah Telaah, 2026)
This study examines how literacy is constructed in Indonesian policy, curriculum, assessment, and implementation guidance for primary and lower secondary education. Literacy has become a central indicator of educational quality in Indonesia, but the policy field contains several documents that use related yet not always identical terms, priorities, and implementation expectations. This study uses qualitative content analysis of national literacy policy documents, curriculum regulations, learning and assessment guidelines, Minimum Competency Assessment materials, School Literacy Movement guidelines, and Rapor Pendidikan documents. The analysis focuses on five dimensions: the meaning of literacy, competency domains, progression from primary to lower secondary schooling, assessment expectations, and the role of schools and teachers. The study shows that literacy is framed not only as reading habit but also as comprehension, reasoning, information use, text production, and cross-curricular learning. However, policy coherence still requires clearer vertical progression between school levels and stronger alignment between curriculum expectations, assessment signals, and school-based implementation guidance. The article argues for a more integrated literacy framework that helps schools translate national expectations into systematic learning and assessment practices